Sovereign yield spreads in the EMU : crisis and structural determinants - Afonso, António (2017)
We use a panel of 11 EMU countries in the period 2000-2014 to assess the importance of political and economic determinants as explanatory factors in sovereign bond yield spreads. According to the results, there is evidence that those spread determinants gained importance after the beginning of the financial crisis. Following the crisis, the debt ratio, fiscal balance, expenditure on pension funds, the level of liquidity, GDP growth rate, and structural reforms have become relevant determinants of sovereign spreads, while fiscal rules have reduced spreads.